Determination of Iodine Concentration in Commonly Consumed Salt and Its Potential Impact on Household Consumers: An Examination and Assessment of Consumed Salt - Md Shahedul Islam; Mohammad Asadul Habib; Mohammad Anwar Ul Alam; Oumma Halima; Nusrat Parvin; Md. Rezaul Karim; Abdur Rahman Shanna; Rifat Jahan Romel; Abdur Rahman Sakib; Mohammad Ariful Islam (Public Health Challenges)
ABSTRACT Introduction Iodine deficiency disorder (IDD) can lead to health issues as it is necessary for metabolic functions. This study investigated the iodine content of commonly consumed salt and the potential impact on daily iodine requirements and IDDs. Methods A cross‐sectional survey was employed using multistage cluster sampling among 240 households, dividing them into eight clusters from four stratified areas. The sampled salts were analyzed using the World Health Organization's iodometric titration method. Results The study revealed that most salt samples from the studied brands had an iodine content within the Bangladesh Standards and Testing Institution (BSTI) recommended range of 20–50 ppm, with two exceptions. The study found that most socioeconomic groups in cities, towns, and semirural areas meet their daily iodine requirements at over 100%. At the same time, many rural homes, regardless of income, fail to meet these requirements. However, the study found iodized salt in 97.9% of all surveyed households. Although 48.3% of unions, that is, rural respondents, was knowledgeable about the existence of iodized salt, 66.7% of respondents was not aware of the health benefits of iodized salt. Surprisingly, 63.3% of the town's household members and 61.7% of the rural population still consume raw salt. Additionally, 79.6% of individuals reported having no IDDs. However, only 44.2% of thyroid patients used iodine supplements. Conclusion Although salt usage and consumption practices are satisfactory, there are still a few concerns about the 100% iodization of branded and raw salts. As a result, many households need help to satisfy their daily iodine requirements.